The latest evidence for possible HIV-1 curative strategies - Hanh Thi Pham; Thibault Mesplède (BioExcel Publishing Ltd, 2018)
Abstract Human immunodeficiency virus type 1 (HIV-1) infection remains a major health issue worldwide. In developed countries, antiretroviral therapy has extended its reach from treatment of people living with HIV-1 to post-exposure prophylaxis, treatment as prevention, and, more recently, preexposure prophylaxis. These healthcare strategies offer the epidemiological tools to curve the epidemic in rich settings and will be concomitantly implemented in developing countries. One of the remaining challenges is to identify an efficacious curative strategy. This review manuscript will focus on some of the current curative strategies aiming at providing a sterilizing or functional cure to HIV-1-positive individuals. These include the following: early treatment initiation in post-treatment controllers as a long-term HIV-1 remission strategy, latency reversal, gene editing with or without stem cell transplantation, and antibodies against either the viral envelope protein or the host integrin α4β7.